Whole exome sequencing diagnosis of inborn errors of metabolism and other disorders in United Arab Emirates - Al-Shamsi, Aisha (Orphanet J Rare Dis, 2016)
BACKGROUND: This study reports on the use of whole exome sequencing (WES) to diagnose children with inborn errors of metabolism and other disorders in United Arab Emirates. METHODS: From January 2012 to December 2014, 85 patients (46 % females) were seen in the metabolic center at Tawam Hospital (Abu Dhabi) and WES testing was requested because definitive diagnoses were not reached by conventional methods. RESULTS: Eighty (93 %) patients were <18 years old and 44 (52 %) were <5 years. Sixty-eight (80 %) patients had neurologic abnormalities. WES facilitated rapid diagnosis in 50 % of the patients, especially those with mitochondrial disorders. Yet, in most cases extensive investigation was required after the results were available. Most patients with confirmed molecular diagnoses had autosomal recessive disorders and were homozygous for the rare alleles. Most patients with autosomal dominant disorders and all patients with X-linked disorders had de novo mutations. WES results were negative (no pathogenic variants related to patient phenotype were identified) in six patients and incorrect in two patients. One patient had a reported “deleterious” hemizygous mutation in SLC35A2, c.617_620del (p.Q206fs), suggesting ‘congenital disorder of glycosylation, TYPE IIm’, but glycosylation studies were normal and healthy brothers had the same mutation. Another patient had “pathogenic” mutation in MCCC2, c.1015G > A (p.V339M), but urine organic acids was normal. WES confirmed inborn errors of metabolism (five mitochondrial diseases, three lysosomal storage diseases, and six other disorders) in 14 patients and genetic disorders (14 neurological diseases and three non-neurological diseases) in 17 patients. Variants of unknown significance were identified in 48 patients; 12 had “confirmed pathologic variants”and 12 had “likely pathologic variants”, based on consistent phenotypes, biochemical/ segregation studies, or reported pathogenicity. In 24 patients, the variants were inconsistent with phenotypes or biochemical/ familial studies. CONCLUSIONS: Although WES provided molecular diagnoses, the results required careful interpretations and many patients required additional investigations. This tool is useful when conventional diagnostic methods fail. Staff competence in obtaining consent/ permission, interpreting the findings, and providing the proper counseling are essential before incorporating this technology into routine clinical practices.